Pious approach to development: social capital and pertubuhan Jamaah Islah Malaysia (JIM) - Malik, Maszlee; Mat, Hamidah (IDOSI, 2014)
Culture, religion, social networks and family institutions are proposed by some researchers to have their significant role in the re-constructed concept of development through the emerging framework of ‘social capital’. The social capital-inspired efforts to development transcends beyond growth and materialistic barometer. In the mean time, Islamic revivalism, from the other side of the coin, has managed to produce Islamic movements all around the world to be active actors of this new framework of development. Islamic movements are believed to be significantly contributory towards the development process through their specific ontological-based worldview that in many cases managed to provide welfare and charity to the people beyond the conventional state-based welfare system. Pertubuhan Jamaah Islah Malaysia as an Islamic movement, during its 22 years of existence (1990-2012) has its considerable amount of contribution to this field. This paper aims to explore the organization’s vision, aim, activities, history and its co-relation to development within the framework of ‘Social Capital’.